2012
DOI: 10.1590/s0102-33062012000400023
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade de fungos micorrízicos arbusculares em área de Caatinga, PE, Brasil

Abstract: RESUMO(Diversidade de fungos micorrízicos arbusculares em área de Caatinga, PE, Brasil). O objetivo deste trabalho foi o de determinar a infectividade, a riqueza de FMA e a condição micorrízica da vegetação em área de Caatinga não antropizada. Coleta de solo e raízes foi realizada em Triunfo/PE. Raízes foram examinadas para determinação da colonização micorrízica. O número mais provável (NMP) de propágulos infectivos de FMA foi estimado por diluições sucessivas do solo e a utilização de milho (Zea mays L.) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
2
17
0
5
Order By: Relevance
“…In the Caatinga, the presence of AMF plays an important role in the establishment and maintenance of vegetation (Mello et al, 2012;Sousa et al, 2013), providing constitutes a mechanism for the adaptation of plants to soils with nutrient restrictions. Thus, arbuscular mycorrhizal fungi present variable tolerance to changes in the environment and soil management, responding to these modifications with changes in the number of propagules (Mello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Caatinga, the presence of AMF plays an important role in the establishment and maintenance of vegetation (Mello et al, 2012;Sousa et al, 2013), providing constitutes a mechanism for the adaptation of plants to soils with nutrient restrictions. Thus, arbuscular mycorrhizal fungi present variable tolerance to changes in the environment and soil management, responding to these modifications with changes in the number of propagules (Mello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, arbuscular mycorrhizal fungi present variable tolerance to changes in the environment and soil management, responding to these modifications with changes in the number of propagules (Mello et al, 2012). For this reason, the AMF community is usually considered a good soil indicator (Pagano et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Mello et al (2012) found in their studies, in a preserved caatinga area in Pernambuco, a very low number of glomerospores (1 spore•g -1 soil), when compared to the In the peanut seeds, due to contamination with fungi, disinfestation was performed by immersion in 70% alcohol for 30 seconds, followed by 1 minute in 0.2% sodium hypochlorite, being subsequently rinsed with distilled water and autoclaved (sterilized), seven times (Vincent, 1970modified by Silva, 2012. Sorghum was sown directly in the pots, each pot received 100 seeds at the moment in which the peanut seedlings were transplanted, two seedlings per pot.…”
Section: Resultsmentioning
confidence: 99%
“…A fact that may have been given caused by the high content of organic matter located in the area, which may have benefited the development of organisms that prey on glomerospores (Mello et al, 2012). Or still, as seen in Souza et al (2003), in soils with high levels of P, there is a reduction in their production.…”
Section: Discussionmentioning
confidence: 99%
“…Mello et al (2012) encontraram taxas de colonização inferiores a 10% em solos da Caatinga com altas concentrações de P no solo, pois baixas ou altas concentrações de P no solo podem aumentar ou diminuir a colonização micorrízica. Samarão et al (2011), avaliando diferentes doses de P em plantas de graviola, inoculadas com inóculo nativo, encontraram aumento no percentual de colonização até a dose de 53,5 mg kg -1 de P, indicando que as espécies nativas de FMA são responsivas a pequenas doses de P adicionadas ao substrato.…”
Section: Resultsunclassified